2011
DOI: 10.1586/erd.10.69
|View full text |Cite
|
Sign up to set email alerts
|

Military applications of novel hemostatic devices

Abstract: Hemorrhage remains the leading cause of death in combat and the primary cause of preventable death after civilian trauma. Over the last 10 years, major improvements in hemostatic agents have resulted in new dressings that are replacing gauze as the standard of care for compressible hemorrhage. This has inspired a plethora of hemostatic products, some of which have been used in the combat and civilian sector. These dressings are crucial in their ability to control initial hemorrhage so that transfer to a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 48 publications
0
49
0
3
Order By: Relevance
“…These granular agents are composed of inactive metal oxides, salts, and mineral silicates and are highly porous. Their mechanism of action is thought to be a concentration of clotting factors and platelets in the wound site by rapidly adsorbing water, thereby aiding in clot formation . Due to the mechanism of action, zeolite‐based products such as first and second generation QuikClot ® were shown to cause a severe exothermic reaction upon water adsorption with temperatures ranging from 44 to 95°C and averaging at 67.4°C .…”
Section: Synthetically Derived Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…These granular agents are composed of inactive metal oxides, salts, and mineral silicates and are highly porous. Their mechanism of action is thought to be a concentration of clotting factors and platelets in the wound site by rapidly adsorbing water, thereby aiding in clot formation . Due to the mechanism of action, zeolite‐based products such as first and second generation QuikClot ® were shown to cause a severe exothermic reaction upon water adsorption with temperatures ranging from 44 to 95°C and averaging at 67.4°C .…”
Section: Synthetically Derived Materialsmentioning
confidence: 99%
“…Kaolin, an aluminum silicate similar to zeolite but without notable associated exothermic reactions, replaced zeolite in recent commercial products in the form of an impregnated gauze (Combat Gauze ® ). Kaolin has been shown to activate the intrinsic clotting pathway and is not able to be left in the injury site …”
Section: Synthetically Derived Materialsmentioning
confidence: 99%
“…The prior studies conducted under austere combat conditions may not translate to the civilian setting. These conditions include needing to care for patients during combat, delay in evacuation to a treatment facility, and first treatment facility not being a tertiary facil ity 13. Brown et al conducted a retrospective chart review on 37 uses in a civilian setting by EMS providers after receiving training on the product and its deployment 14.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that kaolin acts by augmenting activation of factors XII and XI, as well as prekallikrein and high-molecular-weight kininogen. [8,21] Recommended by CoTCCC since 2008, QuikClot Combat Gauze ® was approved by FDA in 2013 for external use. Although the only study conducted on the field with soldiers by Ran et al showed an efficacy of 79%, after some animal studies, CoTCCC was confident that this product should be used in the first line of bleeding control attempt (Table 1).…”
Section: Starch Derivativesmentioning
confidence: 99%